Rhododendron rawatii (Ericaceae), a new species from the Western Himalaya, India - Rai, Ishwari Datt; Adhikari, Bhupendra Singh (Phytotaxa, 2012)
A new species of Rhododendron, R. rawatii is illustrated and described from the Western Himalaya. The species is sporadically found in the subalpine–timberline zone of Uttarakhand state. Fascicled white cottony hairs on the abaxial surface in between lateral veins of leaves, bright pink and shine-less corolla and comparatively large calyx with hairy margins distinguish the new species from its nearest ally R. fulgens. The populations of the species were found in two geographically distinct localities in the Rudraprayag and Pithoragarh districts of Uttarakhand state. The distinguishing morphological characters, affinities with other species and various ecological aspects of the new species are discussed here.